Development and characterization of a wild emmer wheat backcross introgression population for hard winter wheat improvement - Price, J.H.; Guttieri, M.J.; Nyine, M.; Akhunov, E. (2025)
Wild emmer wheat (Triticum turgidum subsp. dicoccoides) is the tetraploid progen-itor of hexaploid bread wheat (Triticum aestivum L.) and is known to be a valuablesource of genetic variation for wheat improvement. However, direct evaluation ofwild emmer diversity for agronomic potential has limited value unless performed inthe backgrounds of adapted cultivars. Here, we present a genetic characterization ofa population of 1601 backcross recombinant inbred lines, with an average genomecomposition of 75% bread wheat and 25% wild emmer. Low-coverage whole-genomesequencing allowed introgressions and aneuploidies to be identified at a relativelylow cost per sample. We identified a relatively large proportion of small introgres-sions (median length 38 Mb), and we found introgressions to be distributed across allchromosomes. Approximately 44% of genotyped progeny carried at least one aneu-ploidy, with monosomies being by far the most common. This population, whichwe have denoted as the Great Plains Wild Emmer/Hard Winter Wheat introgressionpopulation (GPWEW-IP), is, to our knowledge, the first introgression populationdeveloped through the direct hybridization of wild emmer wheat and US-adaptedhard winter wheat. We believe that this population represents a valuable resource forwheat breeders and will accelerate the discovery and integration of useful variationfrom wild emmer wheat.